Association between coping of the primary caregiver and the adolescent patient with cancer - Villanueva Leonel, Jaramillo; Rendón-Macías, Mario Enrique; Ríos Covian, Ana (Springer Science and Business Media, 2025)
Background: Coping mechanisms help individuals face adversity, remain stable over time, and can be generalized to various circumstances. Two types are typically distinguished: the active style, aimed at resolving problems, and the passive style, focused on emotional regulation. We hypothesized that passive coping of the primary caregiver (hereafter, primary caregiver [PC]) would affect the adaptive coping of his or her adolescent child with cancer (hereafter, adolescent with cancer [AC]). Objective: To analyze coping styles in adolescents with cancer (ACs) and their primary caregivers (PCs). Materials and methods: This was an analytical cross-sectional study including 116 pairs of an adolescent with cancer (AC) and a primary caregiver (PC). The adolescents completed the Adolescent Coping Scale (ACS), applicable to those aged 9–17 years, while the caregivers completed the Coping Strategies Inventory (CSI). Results: 49% (57/116) of the pairs both used the active coping style, and 14% showed the passive style in both members. No agreement was found between the coping styles of the AC and PC (Kappa = 0.15, 95% confidence interval [CI]: 0.13–0.14, p = 0.13). The multivariate analysis explained 61% of the variance (Nagelkerke pseudo R2 = 0.61; likelihood ratio = 191.4; p = 0.003). Conclusions: Passive coping by the primary caregiver occurred with low frequency, and active coping was favored, similar to that of the adolescent with cancer. ©The authors ©Springer Science and Business Media © BMC Primary Care.
Keywords: Psycho-oncology; Styles; Strategies; Coping; Adolescents; Cancer; Stress